Óleos essenciais no manejo de doenças fúngicas em sementes de espécies nativas do semiárido - Olinto, Francisco Ariclenes (2020)
Craibeira (Tabebuia aurea), pink ipe (Tabebuia pentaphylla), white jurema (Piptadenia stipulacea), ironwood (Libidibia ferrea) sabiá (Mimosa caesalpiniaefolia) are native species of the Caatinga Biome, disseminated by seeds and essential to maintain plant diversity in the Brazilian semiarid region. Thus, the search for pathogen control is necessary, considering the importance of seed quality for the production of healthy plants. The aim of this study was to evaluate the efficiency of essential oils in reducing the incidence of fungi associated with craibeira, ipe-rosa, white jurema, pau-ferro and sabiá seeds, and their interference in physiological quality. The treatments were essential oils of citronella, frankincense, eucalyptus, sunflower, grape seeds, cloves, Melaleuca and rosemary at a concentration of 1 mL. L-1, Captana fungicide and control composed of sterilized distilled water (DE), using 100 seeds per treatment. The sanitary quality of the seeds was determined by the method of incubation in Petri dishes containing a double layer of filter paper moistened with ADE. The physiological quality of seeds was determined based on germination, emergence and vigor tests. The experimental design was completely randomized with ten treatments. Clove essential oil reduced the percentage of incidence of Aspergillus sp. associated with the seeds of craibeira, ipê-rosa, white jurema, pau-ferro and sabiá. For Rhizopus sp., associated with craibeia, ipe-rosa, white jurema and ironwood seeds, frankincense essential oil was more prominent in reducing incidence. Citronella essential oil contributed to the decrease in the percentage of Penicillium sp. and Cladosporium sp. in the seeds of ipe-rose, white jurema, ironwood and sabiá. In relation to Fusarium sp., rosemary essential oil provided an increase in the incidence in pau-ferro and sabiá seeds. Grape seed oil and tea tree seed oil reduced the physiological quality of crabgrass seeds. Rosemary essential oil did not interfere negatively in the physiological quality of ipe-rosa seeds and provided an increase in the percentage of emergence. All essential oils contributed positively to the physiological quality parameters of white jurema seeds. For ironwood seeds, essential oils from grape and clove seeds reduced the physiological quality. Eucalyptus essential oil reduced the physiological quality of sabiá seeds.